PENCEMARAN LINGKUNGAN HIDUP OLEH LIMBAH PABRIK KELAPA SAWIT (Studi Kasus pada PT. X di Desa Y Kabupaten Kuantan Singingi Tahun 2020) - Anugrah, Teguh; Usmita , Fakhri (UIR PRESS, 2022)
The purpose of this study is to describe environmental pollution due to the activities of PT. X in Y Village, Kuantan Singingi Regency in 2020. This research use a qualitative descriptive approach. Based on the results of the study, it was concluded that environmental pollution due to the activities of the PT. X in Y Village, Kuantan Singingi Regency in the form of water, air, and soil pollution. Water pollution can be seen from the black river water closest to the company's activities, so it can no longer be used for bathing, washing and latrine activities, even animals in the water die. Air pollution comes from smoke from factory production activities and also smells from smelly palm oil waste which reaches community settlements which interfere with smell. Meanwhile, from soil pollution, it can be seen that the function of the soil is reduced, so that certain types of plants are able to grow due to the content of certain substances which are higher than the results of palm oil mill waste. Environmental pollution that occurs due to factory activities that are not in accordance with waste management standards, especially during the rainy season, waste is carried by rainwater so that it pollutes the environment.